Consequences of steel tariffs on imported vehicles: the case of US - Angeli, Silvia (2019)
This thesis analyses the effect of US steel tariffs on the volume of vehicles imported from the European Union from April 2002 to August 2005. The intent is to fill part of the gap left by the literature on the effect of tariffs imposed on raw materials on downstream industries. I use an import tax imposed by the US government to apply a difference-in-differences analysis exploring data obtained from “Harmonized System (HS) District-level Data” database developed by US Census Bureau. My difference in differences analysis indicates that while imports of products made mainly of steel react to changes in tariff levels, the flow of vehicles imports is not affected in the same way, showing no significant change between the two periods taken into consideration. My results are robust the introduction of country, commodity and time fixed effects. Finally, robustness checks provide further support to the findings, showing outcome independency from the control group used and the link between the variation in import volumes and the removal of tariffs.